The Association of Systemic Vascular Disease with Right Ventricular Morphology: The MESA-Right Ventricle Study. - Al-Naamani, Nadine. (2017)
Abstract: Systemic vascular stiffness is recognized as one of the major contributors to the development of left ventricular (LV) diastolic dysfunction and heart failure; however little is known about the relationship of systemic vascular stiffness and the right ventricle (RV). Using data from the Multi-Ethnic Study of Atherosclerosis, we explored the association between systemic vascular stiffness measures (total arterial compliance (TAC), systemic vascular resistance (SVR), aortic augmentation index and reflection magnitude) and the RV morphology (RV mass, RV end-systolic volume, RV end-diastolic volume and RV ejection fraction). All analyses were adjusted for allometric, demographic and clinical variables as well as the corresponding LV parameter. A total of 3,842 subjects without clinical cardiovascular disease who had complete data on the systemic vascular measures and the RV measures were included in the analysis. The mean age of the study sample was 61 ± 10 years with 48% males, 39% non-Hispanic white, 25% Chinese-American, 23% Hispanic, and 13% African American participants. Lower TAC and higher SVR were significantly associated with lower RV mass and smaller RV volumes in fully adjusted models. A 1 mL/mmHg increase in TAC was associated with a 2.4 grams greater RV mass, a 3.9 mL larger RVESV and a 7.6 mL larger RVEDV. A 5 Wood unit increase in SVR was associated with a 1.8 grams smaller RV mass, a 4.9 mL smaller RVESV and a 12.3 mL smaller RVEDV. We also found significant effect modification by age and sex for TAC with RV mass and volumes. Similarly, we found significant effect modification by race and age for SVR with RV mass and volumes. Higher aortic augmentation index and reflection magnitude were associated with smaller RV end-diastolic volume. A 1% increase in aortic augmentation index was associated with a 0.2 mL smaller RVEDV and a 1 unit increase in RM was associated with a 10.1 mL smaller RVEDV. We also found significant effect modification by age and sex for aortic augmentation index with RVEDV. Increased systemic vascular stiffness was associated with lower RV mass and smaller RV volumes in a population of adults without clinical cardiovascular disease. Whether therapies that target systemic vascular stiffness can also impact the RV morphology remains to be determined.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: Jessica Paulus.; Committee: Kari Roberts, and Robin Ruthazer.; Keyword: Medicine.